The Memes as a Jargon of Digital Language - Aladro Vico, Eva; Jardón Clemente, María (CIC. Cuadernos de Información y Comunicación, 2022)
This text discusses memes as a new language in the context of digital media. It states various hypotheses about the literacy function of memes, and describes the aspects that relate the pragmatics of the meme with generative and transformational languages. Once the linguistic nature of memes has been established, the text describes them as a sociolect or antilanguage associated with generational groups, subcultures or specific social groups, which through the characteristic operations of sociolects,  access the sense of community, generate specific instances of meaning and defined as a translator system of the previous cultural forms.
Keywords: memes; jargon; sociolect; transformational grammar; semantic diversion; humor